Two Investigations of River Ice. Part 1. A Field Investigation of the Formation and Characteristics of River Ice. Part 2. Preliminary Laboratory Investigations of Ice Jams and Navigation Channels in Ice Covers - Ashton,George D.; Uzuner,M. Secil; Kennedy,John F. (1970)
An investigation of the temperature and velocity characteristics of flow in rivers during the onset and occurrence of ice covers is described. Vertical and lateral temperature and velocity distributions, and ice thickness and configuration were measured in an Iowa river at frequent intervals during the period of ice cover. Variations in the lateral and vertical temperature distributions are reported. (Author)